2018
DOI: 10.1590/1678-4766e2018015
|View full text |Cite
|
Sign up to set email alerts
|

Gall-inducing insects of deciduous and semideciduous forests in Rio Grande do Sul State, Brazil

Abstract: Galls are specific changes induced by insects on plant organs mainly through increases in plant cell number and/or size. Gall diversity is easy to recognize in the field because gallers are mostly species-specific, and thus each gall morphotype can be a proxy for a galling species. Insect galls are virtually unknown in Seasonal Deciduous and Semi-Deciduous forests of southern Brazil. Here, galls and host plants were surveyed between 2015 and 2017 in four forest fragments of Rio Grande do Sul State in these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
10
0
5
Order By: Relevance
“…These differences in floristic composition may also influence the diversity of the gall-inducing fauna (Araújo et al, 2013). Considering the mean number of gall morphotypes per sampled area/fragment, the richness of gall-inducing species recorded in the present study is similar to or greater than that found in other studies (mean of 30, 22 and six morphotypes per area for Coelho et al, 2009, Goetz et al, 2018and Santos et al, 2011.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These differences in floristic composition may also influence the diversity of the gall-inducing fauna (Araújo et al, 2013). Considering the mean number of gall morphotypes per sampled area/fragment, the richness of gall-inducing species recorded in the present study is similar to or greater than that found in other studies (mean of 30, 22 and six morphotypes per area for Coelho et al, 2009, Goetz et al, 2018and Santos et al, 2011.…”
Section: Discussionsupporting
confidence: 78%
“…morphotypes),Goetz et al (2018; 89 morphotypes) andSantos et al (2011; 64 morphotypes) in other areas of Brazilian dry forest. This difference may have been due to the sampling method used, because the present study evaluated only one fragment of dry forest, whileCoelho et al (2009) sampled three, Goetz et al (2018) sampled four, and Santos et al (2011) sampled 11 areas.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Refs. :Maia & Couri 1993, Monteiro et al 1994, Maia & Souza 2013, Maia & Carvalho-Fernandes 2016, Maia & Silva 2016, Goetz et al 2018, Maia 2020a. Host plant: Guapira opposita (Vell.)…”
mentioning
confidence: 99%
“…(Asteraceae) was the unique multi-host species, with six gall morphotypes. All other plant species hosted a single morphotype.In Brazil, Fabaceae, Asteraceae and Myrtaceae are families often cited for their great gall richness, being important flora components of the surveyed localities (e.g Coelho et al 2013, Maia & Mascarenhas 2017, Goetz et al 2018…”
mentioning
confidence: 99%